2001
DOI: 10.1067/mhn.2001.115092
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Loss in Progressive Systemic Sclerosis Patients: A Comparative Study

Abstract: One fourth of PSS patients had a hearing loss affecting the middle and mainly the high frequencies. This is a lower percentage than that reported by other investigators. A significant prevalence of bilateral patulous eustachian tubes was noticed as well. Further investigation is needed for a better understanding of the mechanism of ear damage in PSS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 10 publications
3
37
0
4
Order By: Relevance
“…Of the eight studies that investigated changes, all identified hearing loss in most individuals with SS, and the prevalence in this finding ranged from 20 to 77%. The type of hearing loss was bilateral sensorineural (6,(9)(10)(11)13,16,17) in most cases, corroborating the physiopathology of the systemic disease. However, mixed (11,15,17) and unilateral (13,17) hearing loss were also described in few cases.…”
Section: Resultssupporting
confidence: 56%
See 4 more Smart Citations
“…Of the eight studies that investigated changes, all identified hearing loss in most individuals with SS, and the prevalence in this finding ranged from 20 to 77%. The type of hearing loss was bilateral sensorineural (6,(9)(10)(11)13,16,17) in most cases, corroborating the physiopathology of the systemic disease. However, mixed (11,15,17) and unilateral (13,17) hearing loss were also described in few cases.…”
Section: Resultssupporting
confidence: 56%
“…The most used study design for describing auditory and vestibular changes in individuals with SS was the crosssectional design, observed in five analyses (10)(11)(12)(13)(14) , followed by four case reports (6,9,15,16) , and one case-control study (17) . Because cross-sectional studies reported findings of a single moment, it was difficult to determine a temporal sequence between exposure to a specific factor and the subsequent development of the disease.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations